2007
DOI: 10.1128/iai.01307-06
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Mice with Lyme Disease Spirochetes Constitutively Producing Outer Surface Proteins A and B

Abstract: Outer surface protein A (OspA) of the Lyme disease spirochete is primarily produced in the tick vector. OspA, which is a receptor for attaching spirochetes to the tick gut, is down regulated as the spirochetes leave the tick and enter the mammalian host. Although OspA is not a major antigen produced in the mammal, the protein appears to be produced under some conditions and production has been linked to more severe disease. A Lyme disease vaccine based on recombinant OspA has been approved for human use. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…IgM dominates the antiborrelial immune response (50), and though it may be too large and unwieldy to penetrate collagenous tissues, it is present in blood and lymph (54). The caveat remains that evidence exists to refute the hypothesis that steric hindrance alone prevents the antibody response from targeting spirochetes embedded in collagen (55,56). As for non-antibody-mediated clearance, recent investigations into invariant natural killer T (iNKT) cells are reminders that there are alternate immune mechanisms to consider (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…IgM dominates the antiborrelial immune response (50), and though it may be too large and unwieldy to penetrate collagenous tissues, it is present in blood and lymph (54). The caveat remains that evidence exists to refute the hypothesis that steric hindrance alone prevents the antibody response from targeting spirochetes embedded in collagen (55,56). As for non-antibody-mediated clearance, recent investigations into invariant natural killer T (iNKT) cells are reminders that there are alternate immune mechanisms to consider (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, DbpA appears to be ineffectively targeted by protective antibodies in mammalian tissues, in sharp contrast to other surface antigens, such as OspC and OspA/B. Constitutive expression of either OspC or OspA/B completely diminishes the ability of B. burgdorferi to cause persistent infection in immunocompetent mice (43,49). A previous study suggested that the interaction of DbpA with decorin may provide B. burgdorferi a protective strategy to evade specific humoral immunity (23).…”
Section: Discussionmentioning
confidence: 99%
“…A fresh blood meal down-regulates OspA/B and up-regulates OspC and other proteins, a process that prepares B. burgdorferi for infection of mammals (12,18,29,42). Repression of OspA/B expression during mammalian infection is critical for the maintenance of the enzootic cycle because their expression would ultimately induce strong humoral responses to effectively block acquisition by the vector (10,45,46), regardless of whether OspA/B can be effectively targeted by borreliacidal antibodies in mammalian tissues (43). B. burgdorferi abundantly expresses OspC during early infection, when the antigen is required (26,44).…”
mentioning
confidence: 99%
“…A fresh blood meal downregulates OspA/B and upregulates OspC and others, a process that prepares B. burgdorferi for infection of mammals (Fingerle et al, 2007;Grimm et al, 2004;Pal et al, 2004;Stewart et al, 2006). The downregulation of OspA and OspB during mammalian infection is critical for the maintenance of the enzootic cycle because their expression would ultimately induce strong humoral responses to effectively block acquisition by the vector (de Silva et al, 1997;Tsao et al, 2001Tsao et al, , 2004, regardless of whether OspA or OspB can be effectively targeted by borreliacidal antibodies in mammalian tissues (Strother et al, 2007). B. burgdorferi abundantly expresses ospC only during early infection when the antigen may be crucial (Grimm et al, 2004;Stewart et al, 2006;Tilly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%